2022
DOI: 10.1002/cbic.202100521
|View full text |Cite
|
Sign up to set email alerts
|

Selective Display of a Chemoattractant Agonist on Cancer Cells Activates the Formyl Peptide Receptor 1 on Immune Cells**

Abstract: Current immunotherapeutics often work by directing components of the immune system to recognize biomarkers on the surface of cancer cells to generate an immune response. However, variable changes in biomarker distribution and expression can result in inconsistent patient response. The development of a more universal tumor‐homing strategy has the potential to improve selectivity and extend therapy to cancers with decreased expression or absence of specific biomarkers. Here, we designed a bifunctional agent that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In addition to the targeted delivery of antigens, the surface display of cancer cell molecules that promote the recruitment of immune cells was investigated ( Sikorski et al, 2022 ). pHLIP was conjugated with a formyl peptide receptor ligand (FPRL) to form FPRL-pHLIP agent.…”
Section: Extracellular Delivery Of Imaging and Therapeutic Payloads B...mentioning
confidence: 99%
“…In addition to the targeted delivery of antigens, the surface display of cancer cell molecules that promote the recruitment of immune cells was investigated ( Sikorski et al, 2022 ). pHLIP was conjugated with a formyl peptide receptor ligand (FPRL) to form FPRL-pHLIP agent.…”
Section: Extracellular Delivery Of Imaging and Therapeutic Payloads B...mentioning
confidence: 99%
“…In addition to successful preclinical and clinical pHLIP-driven intracellular delivery of payloads to tumors (Cheng et al, 2014;Wyatt et al, 2018;Price et al, 2019;Sahraei et al, 2019;Gayle et al, 2021), pHLIPs allow extracellular targeting of cargo molecules for presentation at the surfaces of cells since a pHLIP peptide inserts across the membrane, translocating one terminus into the cytoplasm and leaving the other uninserted terminus in the extracellular space (Hunt et al, 1997;Reshetnyak et al, 2007;Andreev et al, 2010). It has been shown that a pH-dependent pHLIP-mediated decoration of cancer cells with DNP promotes ADCC (Wehr et al, 2020) and that a display of a chemoattractant agonist activates the formyl peptide receptor 1 on immune cells (Sikorski et al, 2022). An additional challenge for all of these immune approaches is to achieve effective presentation of the antigens.…”
Section: Introductionmentioning
confidence: 99%